Chasing the Effects of Pre-Analytical Confounders – A Multicenter Study on CSF-AD Biomarkers - Leitão, Maria João; Baldeiras, Inês; Herukka, Sanna-Kaisa; Pikkarainen, Maria; Leinonen, Ville; Simonsen, Anja Hviid; Perret-Liaudet, Armand; Fourier, Anthony; Quadrio, Isabelle; Veiga, Pedro Mota; de Oliveira, Catarina Resende (Frontiers in Neurology, 2015)
Core cerebrospinal fluid (CSF) biomarkers-Aβ42, Tau and pTau–have been recently incorporated in the revised criteria for Alzheimer’s disease (AD). However, their widespread clinical application lacks standardization. Pre-analytical sample handling and storage play an important role in the reliable measurement of these biomarkers across laboratories. In this study, we aim to surpass the efforts from previous studies, by employing a multicentre approach to assess the impact of less studied CSF pre-analytical confounders in AD-biomarkers quantification. Four different centres participated in this study and followed the same established protocol. CSF samples were analysed for three biomarkers (Aβ42, Tau and pTau) and tested for different spinning conditions (temperature: Room temperature (RT) vs. 4oC; speed: 500g vs. 2000g vs. 3000g), storage volume variations (25%, 50% and 75% of tube total volume) as well as freezing-thaw cycles (up to 5 cyles). The influence of sample routine parameters, inter-centre variability and relative value of each biomarker (reported as normal/abnormal), was analysed. Centrifugation conditions did not influence biomarkers levels, except for samples with a high CSF total protein content, where either non centrifugation or centrifugation at RT, compared to 4ºC, led to higher Aβ42 levels. Reducing CSF storage volume from 75% to 50% of total tube capacity, decreased Aβ42 concentration (within analytical CV of the assay), whereas no change in Tau or pTau was observed. Moreover, the concentration of Tau and pTau appears to be stable up to 5 freeze-thaw cycles, whereas Aβ42 levels decrease if CSF is freeze-thawed more than 3 times. This systematic study reinforces the need for CSF centrifugation at 4ºC prior to storage and highlights the influence of storage conditions in Aβ42 levels. This study contributes to the establishment of harmonized standard operating procedures that will help reducing inter-lab variability of CSF-AD biomarkers evaluation.